In-Memory Data Management An Inflection Point for Enterprise Applications - Plattner, Hasso; Zeier, Alexander 1969-.; SpringerLink (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
In the last 50 years the world has been completely transformed through the use of IT. We have now reached a new inflection point. Here we present, for the first time, how in-memory computing is changing the way businesses are run. Today, enterprise data is split into separate databases for performance reasons. Analytical data resides in warehouses, synchronized periodically with transactional systems. This separation makes flexible, real-time reporting on current data impossible. Multi-core CPUs, large main memories, cloud computing and powerful mobile devices are serving as the foundation for the transition of enterprises away from this restrictive model. We describe techniques that allow analytical and transactional processing at the speed of thought and enable new ways of doing business. The book is intended for university students, IT-professionals and IT-managers, but also for senior management who wish to create new business processes by leveraging in-memory computing.
Foreword by Prof. John L. Hennessy (Stanford University, California, USA) and Prof. David A. Patterson (University of California at Berkeley, USA). - Preface . Introduction. - PART I An Inflection Point for Enterprise Applications . - 1 Desirability, Feasibility, Viability The Impact of In-Memory . - 2 Why Are Enterprise Applications So Diverse . - 3 SanssouciDB ?Blueprint for an In-Memory Enterprise Database System . - PART II SanssouciDB A Single Source of Truth through In-Memory. - 4 The Technical Foundations of SanssouciDB . - 5 Organizing and Accessing Data in SanssouciDB -- PART III How In-Memory Changes the Game . - 6 Application Development . - 7 Finally, a Real Business Intelligence System Is at Hand -- 8 Scaling SanssouciDB in the Cloud . - 9 The In-Memory Revolution Has Begun . - References . - Glossary . - Abbreviations . - Index.
Electronic reproduction.
Keywords: Database management; Enterprise application integration (Computer systems); Business -- Data processing; Electronic books